The Effect of Leisure‐Time Physical Activity on Obesity, Diabetes, High BP and Heart Disease Among Canadians: Evidence from 2000/2001 to 2005/2006. (23rd September 2014) - Sarma, Sisira; Devlin, Rose Anne; Gilliland, Jason; Campbell, M. Karen; Zaric, Gregory S.
Abstract: Although studies have looked at the effect of physical activity on obesity and other health outcomes, the causal nature of this relationship remains unclear. We fill this gap by investigating the impact of leisure‐time physical activity (LTPA) and work‐related physical activity (WRPA) on obesity and chronic conditions in Canadians aged 18–75 using instrumental variable and recursive bivariate probit approaches. Average local temperatures surrounding the respondents' interview month are used as a novel instrument to help identify the causal relationship between LTPA and health outcomes. We find that an active level of LTPA (i.e. walking ≥1 h/day) reduces the probability of obesity by five percentage points, which increases to 11 percentage points if also combined with some WRPA. WRPA exhibits a negative effect on the probability of obesity and chronic conditions. Copyright © 2014 John Wiley & Sons, Ltd.